Observed Prevalence and Characterization of Fluoroquinolone-Resistant and Multidrug-Resistant Bacteria in Loggerhead Sea Turtles (Caretta caretta) from the Adriatic Sea - Olimpia Lai; Antonella Tinelli; Simona Soloperto; Giuseppe Crescenzo; Domenico Galante; Angela Calarco; Magda Tribuzio; Viviana Manzulli; Giulia Caioni; Claudia Zizzadoro; Antonella Damiano; Antonio Camarda; et al. (Antibiotics)
Background/Objectives: Antimicrobial resistance (AMR) is a major global health concern with profound implications for human, animal, and environmental health. Marine ecosystems are emerging as reservoirs of resistant bacteria due to contamination from anthropogenic activities. This study aimed to investigate fluoroquinolone-resistant and multidrug-resistant bacteria in loggerhead sea turtles (Caretta caretta). Methods: Cloacal swabs were collected from 28 loggerhead sea turtles at a rescue center in southern Italy. Swabs were cultured in nutrient media supplemented with enrofloxacin. Bacterial isolates underwent identification by MALDI-TOF, antimicrobial susceptibility testing, and assessment for multidrug resistance. Conjugation experiments evaluated the transferability of enrofloxacin resistance. Results: Thirty-six enrofloxacin-resistant bacterial strains were isolated from 22 turtles. The identified species included Vagococcus fluvialis (13 strains), Citrobacter freundii (5), Escherichia coli (6), and Pseudomonas mendocina (4). Thirty-five isolates exhibited multidrug resistance, with resistance to critically important antibiotics such as imipenem observed in C. freundii and Enterobacter faecium. Conjugation experiments showed no transfer of resistance genes. Conclusions: The study highlights the prevalence of fluoroquinolone-resistant and multidrug-resistant bacteria in C. caretta, implicating marine environments as reservoirs of AMR. The findings underscore the need for stricter regulation of antimicrobial use and monitoring of resistance dissemination in marine ecosystems. These results contribute to understanding AMR dynamics within the One Health framework, emphasizing the interconnectedness of environmental, animal, and human health.